2015
DOI: 10.1016/j.jhep.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat in patients with non-alcoholic fatty liver disease

Abstract: We recently reported that epicardial fat thickness is significantly associated with the severity of liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD), and that in this clinical setting, morphological and functional cardiac alterations by echocardiography are inversely related with the severity of liver damage [1]. Of note, these associations were maintained after correction for both cardiometabolic and hepatic confounders including visceral adiposity.In their letter [10], Corrao and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Karabay and colleagues observed no significant differences in cardiac function among adult patients with and without NASH; however, the authors relied on assessments of standardized mean differences between patients and controls without accounting for potential covariates . Most recently, in an analysis of 147 consecutive adults with histologically confirmed NAFLD, no significant differences in LV mass, E:A ratio, or early annular diastolic tissue velocity were found in a multivariable model comparing those with and without NASH; however, that study did not include normal histological controls, and the population had a remarkably high rate of both prevalent NASH (76%) and visceral obesity (85%), suggesting advanced underlying cardiometabolic disease, which could limit the generalizability of their results . Though small in size, our study benefits from the availability of comparable patient controls with normal hepatic histology.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Karabay and colleagues observed no significant differences in cardiac function among adult patients with and without NASH; however, the authors relied on assessments of standardized mean differences between patients and controls without accounting for potential covariates . Most recently, in an analysis of 147 consecutive adults with histologically confirmed NAFLD, no significant differences in LV mass, E:A ratio, or early annular diastolic tissue velocity were found in a multivariable model comparing those with and without NASH; however, that study did not include normal histological controls, and the population had a remarkably high rate of both prevalent NASH (76%) and visceral obesity (85%), suggesting advanced underlying cardiometabolic disease, which could limit the generalizability of their results . Though small in size, our study benefits from the availability of comparable patient controls with normal hepatic histology.…”
Section: Discussionmentioning
confidence: 98%
“…It is hypothesized that the pathogenesis of cardiac dysfunction in NAFLD is related to the release of inflammatory cytokines among those with nonalcoholic steatohepatitis (NASH) . However, data in patients with biopsy‐proven NAFLD are limited, and the few published analyses of this relationship using histologically defined NASH have yielded conflicting results . Thus, it remains unknown whether histological NASH is associated with subclinical cardiac remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study was a comparison of the means between NAFLD patients and controls and did not take into consideration covariates. Petta et al [15] in a multivariate model found no significant differences in left ventricular mass or early annular diastolic tissue velocity in NAFLD patients. Our results are consistent with Simon et al [16], but given the conflicting evidence in the literature future studies are needed to further validate our results.…”
Section: Discussionmentioning
confidence: 89%
“…Petta et al . [ 15 ] in a multivariate model found no significant differences in left ventricular mass or early annular diastolic tissue velocity in NAFLD patients. Our results are consistent with Simon et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation